A twentieth century perspective on summer Antarctic pressure change and variability and contributions from tropical SSTs and ozone depletion. Issue 19 (6th October 2017) - Fogt, Ryan L.; Goergens, Chad A.; Jones, Julie M.; Schneider, David P.; Nicolas, Julien P.; Bromwich, David H.; Dusselier, Hallie E.
Abstract: During the late twentieth century, the Antarctic atmospheric circulation has changed and significantly influenced the overall Antarctic climate, through processes including a poleward shift of the circumpolar westerlies. However, little is known about the full spatial pattern of atmospheric pressure over the Antarctic continent prior to 1979. Here we investigate surface pressure changes across the entire Antarctic continent back to 1905 by developing a new summer pressure reconstruction poleward of 60°S. We find that only across East Antarctica are the recent pressures significantly lower than pressures in the early twentieth century; we also discern periods of significant positive pressure trends in the early twentieth century across the coastal South Atlantic sector of Antarctica. Climate model simulations reveal that both tropical sea surface temperature variability and other radiative forcing mechanisms, in addition to ozone depletion, have played an important role in forcing the recent observed negative trends. Key Points: Only East Antarctica has significant negative summer pressure decreases since 1905 The coastal South Atlantic sector of Antarctica displays positive summer pressure trends in the first half of the twentieth century Multiple factors, including tropical sea surface temperature variability, explain the recent negative summer Antarctic pressure trends Plain Language Summary: Since most Antarctic meteorological observations start around 1957, very little is known about atmospheric pressure variability across Antarctica throughout the entire twentieth century. Yet changes in the atmospheric circulation around Antarctica have been linked to warming across West Antarctica, the lack of warming in East Antarctica, and changes in the sea ice surrounding Antarctica. To better understand the significance of these changes in a historical context, a new spatially complete summer pressure reconstruction is generated and evaluated in this paper. Through the high quality of this reconstruction, we determine that only across East Antarctica are pressure changes significant when in context of the full twentieth century; over portions of the South Atlantic coastal sector of Antarctica, the early twentieth century was marked with pressure increases. Using a suite of climate model simulations, we determine that other factors, including tropical sea surface temperatures, are needed in order to fully replicate the recent negative summer pressure trends that have occurred across the entire continent. This work therefore highlights the role of natural variability in Antarctic pressure during the twentieth century, and the need to consider multiple mechanisms beyond ozone depletion to understand recent Antarctic pressure changes.